Trailing clouds : immigrant fiction in contemporary America - Cowart, David, 1947- (Cornell paperbacks., 2006)
"We stand to learn much about the durability of or changes in the American way of life from writers such as Bharati Mukherjee (born in India), Ursula Hegi (born in Germany), Jerzy Kosinski (born in Poland), Jamaica Kincaid (born in Antigua), Cristina Garcia (born in Cuba), Edwidge Danticat (born in Haiti), Wendy Law-Yone (born in Burma), Mylène Dressler (born in the Netherlands), Lan Cao (born in Vietnam), and such Korean-born authors as Chang-rae Lee, Theresa Hak Kyung Cha, and Nora Okja Keller-writers who in recent years have come to this country and, in their work, contributed to its culture."-David CowartIn Trailing Clouds, David Cowart offers fresh insights into contemporary American literature by exploring novels and short stories published since 1970 by immigrant writers. Balancing historical and social context with close readings of selected works, Cowart explores the major themes raised in immigrant writing: the acquisition of language, the dual identity of the immigrant, the place of the homeland, and the nature of citizenship.Cowart suggests that the attention to first-generation writers (those whose parents immigrated) has not prepared us to read the fresher stories of those more recent arrivals whose immigrant experience has been more direct and unmediated. Highlighting the nuanced reflection in immigrant fiction of a nation that is ever more diverse and multicultural, Cowart argues that readers can learn much about the changes in the American way of life from writers who have come to this country, embraced its culture, and penned substantial literary work in English.